ADMINISTRATIVE-LEGAL BASES OF FUNCTIONING OF THE CIVIL SERVICE: : COMPARATIVE-LEGAL ASPECT - Horban, Oleksandr; Bass, Viktoriya; Drozd, Oleksii; Kalatur, Maksym; Shkarupa, Kostiantyn (Revista Gênero e Interdisciplinaridade, 2020)
The topicality of this article is due to the fact that the civil service is a special element of the governmental system of each state, the effective functioning of which provides the observance of constitutional rights and freedoms of citizens, consistent and sustainable development of the country. The purpose of the article is to conduct scientific research on the functioning and overall reform of government control and civil service in Ukraine and in developed countries of the world. The leading research methods are general scientific and specific research methods, including methods of logic, analysis, comparison etc. The results of this study are a comparative and legal analysis of the civil service institute construction in developed countries of the world, the identification of basic problems and consequences of reforming this field in Ukraine. The significance of the obtained results is reflected in the fact that this study may serve as a basis for outlining future changes to the current legislation of Ukraine on the functioning of the civil service and the protection of the rights and legitimate interests of civil servants.